High-tonnage porcelain post insulator as well as blank raw material formula and preparation method thereof

By adjusting the raw material formula of the porcelain pillar insulator, using plate-shaped corundum and potassium feldspar instead of high alumina bauxite, and combining eloite, the problem of unstable slurry in the existing technology has been solved, significantly improving the porcelain The mechanical properties are suitable for ultra-high voltage transmission and transformation systems.

CN119462071APending Publication Date: 2025-02-18SUZHOU PORCELAIN INSULATOR WORKS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411769702.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the raw material formula of existing porcelain pillar insulators, there are many titanium iron impurities in high alumina bauxite, resulting in unstable slurry quality, and the products produced have poor stability in mechanical strength and electrical properties.

Method used

By adjusting the slurry formula, plate-shaped corundum and potassium feldspar are used to replace high-alumina bauxite, combined with nano-sized structures, the amount of mineralizer and dispersant is adjusted to improve the composition stability of the blank slurry and Structural uniformity.

Benefits of technology

It has achieved the improvement of homogeneity of porcelain parts, improved the mechanical properties of porcelain insulators, especially thermal shock resistance and bending strength, and is suitable for ultra-high voltage transmission and transformation systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462071A_ABST
    Figure CN119462071A_ABST
Patent Text Reader

Abstract

The invention discloses a high-tonnage porcelain post insulator, and a blank raw material formula and a preparation method thereof, and belongs to the technical field of electrical porcelain manufacturing. The blank raw material formula of the high-tonnage porcelain post insulator comprises a lean raw material, a clay raw material, a mineralizing agent and a dispersing agent, the barren raw material is composed of tabular corundum and potassium feldspar, and the clay raw material is composed of kaolin, attapulgite and halloysite; according to the weight ratio, the plate-shaped corundum accounts for 30-50 wt%, the potassium feldspar accounts for 10-20 wt%, the kaolin accounts for 15-30 wt%, the attapulgite accounts for 3-10 wt%, and the halloysite accounts for 2-5 wt%, totaling 100 wt%. By adjusting the formula of the slurry, the composition stability and the structural uniformity of the blank slurry are improved, it is guaranteed that a fired porcelain piece has good homogeneity, and the mechanical performance of a porcelain insulator is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of electric porcelain manufacturing, in particular to a high-tonnage porcelain post insulator, a blank raw material formula and a preparation method thereof. Background Art

[0002] As an important power transmission and transformation equipment, porcelain post insulators are widely used in UHV power transmission and transformation projects. Porcelain parts are an important part of porcelain post insulators, and their mechanical properties directly affect the safety and reliability of UHV power transmission and transformation; for example, when the insulator deteriorates, the mechanical strength is significantly reduced, which will cause serious accidents such as pole breakage and damage. The performance of porcelain parts depends on the formula and preparation process of the blank and glaze layer.

[0003] For UHV power transmission and transformation projects, the blanks generally use high-alumina bauxite, clay, etc. as the main raw materials. However, high-alumina bauxite contains many titanium-iron impurities and has high quality control requirements. If no additional impurity removal operations are performed, the slurry quality will be unstable and the resulting products will have poor stability in mechanical strength and electrical properties.

[0004] In order to solve the above problems in the prior art, the present invention is provided. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a high-tonnage porcelain post insulator, a raw material formula for its blank and a preparation method. By adjusting the slurry formula, the composition stability of the blank slurry and the uniformity of the blank structure are improved, ensuring that the fired porcelain parts have good homogeneity, thereby improving the mechanical properties of the porcelain insulator.

[0006] The first aspect of the present invention relates to a raw material formula for a blank of a high-tonnage porcelain post insulator, comprising: a barren raw material, a clay raw material, a mineralizer and a dispersant;

[0007] The barren raw material is composed of plate-like corundum and potassium feldspar, and the clay raw material is composed of kaolin, attapulgite and halloysite; according to the weight ratio, the plate-like corundum is 30-50wt%, the potassium feldspar is 10-20wt%, the kaolin is 15-30wt%, the attapulgite is 3-10wt%, and the halloysite is 2-5wt%, totaling 100wt%;

[0008] The amount of mineralizer added is 0.5% to 3% of the total weight of the barren raw material and clay raw material, and the amount of dispersant added is 0.15% to 0.4% of the total weight of the barren raw material and clay raw material;

[0009] Preferably, the fineness of the plate-like corundum and kaolin is less than 1.5% on a 400-mesh sieve, and the fineness of the potassium feldspar, mineralizer and dispersant is less than 1.2% on a 300-mesh sieve.

[0010] Preferably, the weight proportion of aluminum oxide in the plate-like corundum is not less than 98%.

[0011] Preferably, the weight proportion of potassium oxide in potassium feldspar is not less than 10%.

[0012] Preferably, the kaolin is Suzhou clay, and the plasticity index is greater than 3.6.

[0013] Preferably, the weight proportion of iron oxide in attapulgite is not more than 1.5%.

[0014] Preferably, the purity of halloysite is not less than 96%, the diameter is 80 nm, and the length is 0.5 to 2 μm.

[0015] Preferably, the mineralizer is at least one of barium carbonate and chlorite.

[0016] Preferably, the dispersant is at least one of sodium hexametaphosphate and sodium tripolyphosphate.

[0017] The second aspect of the present invention relates to a method for preparing a high-tonnage porcelain post insulator, comprising the steps of manufacturing an insulator porcelain part:

[0018] According to the above blank raw material formula, the raw materials are weighed, and then water is added to grind them. After the residue on the 400-mesh sieve is less than 1.0%, the slurry is released, and the slurry is subjected to iron removal, filter pressing dehydration, rough smelting, aging, vacuum extrusion, blank shaping, drying, glazing and sanding, and then fired in a kiln with a reducing flame to obtain a porcelain piece;

[0019] The firing process is as follows: heating from room temperature to 120°C over 4 to 8 hours, keeping at 120°C for 2 hours; heating to 400°C over 4 to 8 hours; heating to 900°C over 4 to 6 hours; keeping at 900°C for 4 hours; finally heating to 1050-1220°C over 3 to 6 hours, and then cooling naturally with the kiln.

[0020] Preferably, the number of iron removal is three times, and the content of iron oxide in the slurry after three iron removals is not more than 1.5wt%; under the condition that the content of iron oxide impurities in the raw materials is controlled to be no more than 1.5wt%, the main purpose of iron removal is to remove excess iron oxide impurities introduced during the process through equipment such as ball milling equipment, slurry conveying pipelines, stirring blades, etc.

[0021] Preferably, the residual moisture content after filter pressing and dehydration is 1.2±0.2wt%.

[0022] Preferably, the aging time is 15 to 24 hours.

[0023] Preferably, after glazing and sanding treatment and before firing, the blank is baked at a temperature of 40±5° C. in a dry environment for 60 to 72 hours.

[0024] The third aspect of the present invention relates to a high-tonnage porcelain post insulator, which is made by the above method and has a rated bending failure load of not less than 16kN; it can be applied to ultra-high voltage transmission and transformation systems. The ultra-high voltage is divided into ultra-high voltage AC and ultra-high voltage DC, where ultra-high voltage AC (UHV) refers to voltages of 1000kV and above, and ultra-high voltage DC refers to voltages of ±800kV and above.

[0025] Compared with the prior art, the present invention has the following technical effects:

[0026] 1) Using plate-shaped corundum to replace high-alumina bauxite has less titanium iron impurities and relatively simple impurity removal operation; in addition, compared with high-purity industrial alumina, high-purity plate-shaped corundum has a larger grain size, which improves the thermal shock resistance of ceramic parts; combined with the nano-sized structure and kaolin-like properties of halloysite, the defect of large particle size of barren raw materials is overcome. On this basis, the stable crystal phase structure of plate-shaped corundum and the special nano-tubular structure of halloysite can be used to improve the toughness and bending strength of ceramic parts after sintering;

[0027] 2) The slurry is often in a relatively static state after completing the previous process and before entering the next process. A large amount of added barren raw materials such as plate-like corundum and potassium feldspar have a high specific gravity and are easy to precipitate, resulting in reduced slurry uniformity. The present invention adds attapulgite, which utilizes its large specific surface area and strong adsorption capacity to effectively disperse the barren raw material particles in the slurry, prevent their sedimentation, and improve the stability of the slurry, thereby obtaining a uniform mud blank, greatly improving the uniformity of the porcelain parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the SEM image of tabular corundum;

[0029] Figure 2 is the SEM image of halloysite;

[0030] Figure 3 It is a cross-sectional view of the porcelain parts in Example 1, the porcelain part a on the left is a porcelain part in porcelain part group one, and the porcelain part b on the right is a porcelain part in porcelain part group two. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The experimental methods without specific conditions in the examples are carried out according to conventional methods and conditions.

[0032] Plate-like corundum (plate-like crystal structure, purity 99%, SEM photo as shown Figure 1 As shown, its crystal surface is clean and the grain size is large), kaolin, potassium feldspar, attapulgite (average particle size 200nm), halloysite (purity 96%, SEM photo as shown Figure 2As shown, the diameter is 80nm and the length is about 1μm), barium carbonate (purity 96%), chlorite (pseudohexagonal platelet crystal structure), sodium hexametaphosphate (purity 99%) and sodium tripolyphosphate (purity 99%) are all commercially available.

[0033] Example 1

[0034] The process of making high-tonnage porcelain post insulators in this embodiment is as follows:

[0035] (1) According to the weight ratio of 40:30:15:10:5:0.2:0.3:0.2, plate-shaped corundum, kaolin, potassium feldspar, attapulgite, halloysite, barium carbonate, chlorite and sodium hexametaphosphate are weighed, added into a ball mill and then ball-milled with water; after ball-milling, the slurry fineness reaches the standard of less than 1.0% on a 400-mesh sieve, and then sieved and discharged;

[0036] (2) The slurry is then subjected to three iron removal treatments, and then excess water is filtered out by a filter press to obtain a mud material; the mud material is roughly smelted and transported to a silo for aging until the moisture content in the mud material does not exceed 1.2wt%;

[0037] (3) The aged mud is squeezed into mud segments by a large vacuum mud kneading machine;

[0038] (4) Place the clay segments on the molding machine, trim and shape the blanks to make blanks, and then place the blanks in the drying room for drying;

[0039] (5) Taking part of the dried white blank for glazing and sanding, the glazing is carried out by high-speed atomization spraying process. The glazed blank is put back into the drying room and baked at 40°C for 60 to 72 hours;

[0040] (6) The dried but unglazed white blanks in step 4 are taken as one group, and the baked glazed blanks in step 5 are taken as two groups. They are loaded into kilns respectively and fired with reducing flame. The firing curve is as follows: the temperature is raised from room temperature to 120°C over 4 hours, and kept at 120°C for 2 hours; then the temperature is raised to 400°C over 4 hours; then the temperature is raised to 900°C over 6 hours; kept at 900°C for 4 hours; finally, the temperature is raised to 1050°C over 6 hours; and then cooled naturally in the kiln to obtain porcelain pieces in group one and porcelain pieces in group two.

[0041] (7) The first group of porcelain parts and the second group of porcelain parts are glued together to obtain porcelain insulators.

[0042] After testing, the material properties in this embodiment are shown in Table 1.

[0043] Table 1 Material properties

[0044] Example 2

[0045] The difference between this embodiment and embodiment 1 is that:

[0046] I) weighing plate-like corundum, kaolin, potassium feldspar, attapulgite, halloysite, barium carbonate, chlorite and sodium tripolyphosphate in a weight ratio of 45:25:15:10:5:0.3:0.4:0.3, adding the mixture into a ball mill and then grinding the mixture with water;

[0047] II) The firing curve is as follows: the temperature is raised from room temperature to 120°C over 4 hours, and kept at 120°C for 2 hours; the temperature is then raised to 400°C over 4 hours; the temperature is then raised to 900°C over 6 hours; the temperature is kept at 900°C for 4 hours; the temperature is finally raised to 1120°C over 6 hours, and then naturally cooled in the kiln.

[0048] After testing, the material properties in this embodiment are shown in Table 2.

[0049] Table 2 Material properties

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that:

[0052] I) weighing plate-like corundum, kaolin, potassium feldspar, attapulgite, halloysite, barium carbonate, chlorite, sodium tripolyphosphate and sodium hexametaphosphate in a weight ratio of 50:20:20:5:5:0.3:0.4:0.2:0.2, adding the mixture into a ball mill and then grinding the mixture with water;

[0053] II) The firing curve is as follows: the temperature is raised from room temperature to 120°C over 4 hours, and kept at 120°C for 2 hours; the temperature is raised to 400°C over 4 hours; the temperature is then raised to 900°C over 6 hours; the temperature is kept at 900°C for 4 hours; the temperature is finally raised to 1160°C over 6 hours, and then naturally cooled in the kiln.

[0054] After testing, the material properties in this embodiment are shown in Table 3.

[0055] Table 3 Material properties

[0056] Comparative Example 1

[0057] Compared with Example 1, the only difference of this comparative example is that industrial alumina powder with a 400-mesh sieve residue of less than 1.5% is used instead of plate-like corundum.

[0058] After testing, the material properties in this embodiment are shown in Table 4.

[0059] Table 4 Material properties

[0060] Comparative Example 2

[0061] Compared with Example 1, the difference of this comparative example is only that:

[0062] I) According to the weight ratio of 40:45:15:0.2:0.3:0.2, plate-like corundum, kaolin, potassium feldspar, barium carbonate, chlorite and sodium hexametaphosphate were weighed, added into a ball mill and then ball-milled with water, without adding attapulgite and halloysite.

[0063] After testing, the material properties in this embodiment are shown in Table 5.

[0064] Table 5 Material properties

[0065] Comparative Example 1 and Comparative Examples 1-2: The present invention significantly improves the mechanical properties of porcelain parts by adding attapulgite and halloysite.

[0066] Comparative Examples 1 to 3: With the increase of the content of the lean raw material component, the maximum firing temperature increased, and the mechanical properties of both porcelain group 1 and porcelain group 2 were improved; while the reduction of the attapulgite and halloysite content did not lead to a decrease in the mechanical properties of the porcelain, indicating that the content of the lean raw materials plays a dominant role in the mechanical properties.

[0067] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A raw material formula for a high-tonnage porcelain post insulator blank, characterized in that: include: Barren raw materials, clay raw materials, mineralizers and dispersants; The barren raw material is composed of plate-like corundum and potassium feldspar, and the clay raw material is composed of kaolin, attapulgite and halloysite; according to the weight ratio, the plate-like corundum is 30-50wt%, the potassium feldspar is 10-20wt%, the kaolin is 15-30wt%, the attapulgite is 3-10wt%, and the halloysite is 2-5wt%, totaling 100wt%; The amount of mineralizer added is 0.5% to 3% of the total weight of the barren raw material and clay raw material, and the amount of dispersant added is 0.15% to 0.4% of the total weight of the barren raw material and clay raw material; Preferably, the fineness of the plate-like corundum and kaolin is less than 1.5% on a 400-mesh sieve, and the fineness of the potassium feldspar, mineralizer and dispersant is less than 1.2% on a 300-mesh sieve.

2. The blank raw material formula according to claim 1, characterized in that: The weight proportion of aluminum oxide in the plate-like corundum is not less than 98%, the weight proportion of potassium oxide in the potassium feldspar is not less than 10%, and the weight proportion of iron oxide in the attapulgite is not more than 1.5%.

3. The blank raw material formula according to claim 1, characterized in that: The purity of the halloysite is not less than 96%, the diameter is 80nm, and the length is 0.5-2μm.

4. The blank raw material formula according to claim 1, characterized in that: The mineralizer is at least one of barium carbonate and chlorite.

5. The blank raw material formula according to claim 1, characterized in that: The dispersant is at least one of sodium hexametaphosphate and sodium tripolyphosphate.

6. A method for preparing a high-tonnage porcelain post insulator, characterized in that: The manufacturing steps of insulator porcelain parts include: According to the blank raw material formula of any one of claims 1 to 5, the raw materials are weighed, and then water is added to grind them, and the slurry is discharged after reaching the 400-mesh sieve requirement, and the slurry is subjected to iron removal, filter pressing dehydration, rough smelting, aging, vacuum extrusion, blank shaping, drying, glazing and sanding, and then fired in a kiln with a reducing flame to obtain a porcelain piece; The firing process is as follows: heating from room temperature to 120°C over 4 to 8 hours, keeping at 120°C for 2 hours; heating to 400°C over 4 to 8 hours; heating to 900°C over 4 to 6 hours; keeping at 900°C for 4 hours; finally heating to 1050-1220°C over 3 to 6 hours, and then cooling naturally with the kiln.

7. The preparation method according to claim 6, characterized in that: The iron removal process was repeated three times, and the content of iron oxide in the slurry after the three iron removal processes was no more than 1.5 wt %.

8. The preparation method according to claim 6, characterized in that: The residual moisture content after filter pressing and dehydration was 1.2±0.2wt%.

9. The preparation method according to claim 6, characterized in that: After glazing and sanding and before firing, the blank is baked in a dry environment at a temperature of 40±5℃ for 60 to 72 hours.

10. A high-tonnage porcelain post insulator, characterized in that: It is made by any one of the preparation methods described in claims 6 to 9, and has a rated bending failure load of not less than 16 kN.